1970
DOI: 10.1104/pp.45.3.255
|View full text |Cite
|
Sign up to set email alerts
|

The Biosynthesis of Steryl Glucosides in Plants

Abstract: UDP-galactose-'4C, uniformly labeled in the galactose moiety, and UDP-glucose-l4C, uniformly labeled in the glucose moiety, were purchased from New England Nuclear. UDP-galactose-'2C was purchased from Calbiochem. UDP-glucose-12C was purchased from Pabst. Silica Gel G was obtained from Brinkman and silicic acid (Bio-Sil A, 100-200 mesh) was obtained from Calbiochem.Steryl glucosides have been known to exist in plants for some time (21), but the existence of acylated steryl glucosides has been recognized only r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
45
0

Year Published

1970
1970
1990
1990

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 18 publications
5
45
0
Order By: Relevance
“…The identification of fractions 3 and 4 were confirmed by hydrolyzing the acyl steryl glycoside fraction for 3 hr at 40 C with 0.5 N NaOH. Mild alkaline hydrolysis removes the fatty acid from the acyl steryl glycoside, converting it to steryl glycoside (22). Rechromatographing on a thin layer plate and on a silicic acid column showed that the acyl steryl glycoside fraction 3 was converted to steryl glycoside, fraction 4 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The identification of fractions 3 and 4 were confirmed by hydrolyzing the acyl steryl glycoside fraction for 3 hr at 40 C with 0.5 N NaOH. Mild alkaline hydrolysis removes the fatty acid from the acyl steryl glycoside, converting it to steryl glycoside (22). Rechromatographing on a thin layer plate and on a silicic acid column showed that the acyl steryl glycoside fraction 3 was converted to steryl glycoside, fraction 4 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…
Biosynthesis of galactolipids in spinach chloroplasts has been reported (2,5). In these studies uridine diphosphate galactose was used as a galactosyl donor to some endogenous acceptor (diglyceride) (Branson Instruments Inc.).
…”
mentioning
confidence: 99%
“…This is favorable to the production of 1,2-DG from MGDG, but unfavorable to the reverse production of MGDG from 1 ,2-DG. It has been shown that incorporation of UDP-Gal into MGDG is gradually decreased, but incorporation into oligogalactolipids is steadily increased or accelerated when chloroplasts (9,19) and envelopes (5) are incubated for prolonged periods. This observation may be partly accounted for by the inhibition of UDGT and the stimulation of GGGT activity by FFA, since FFA is known to be readily produced by aging of chloroplasts (13,17,22).…”
Section: Discussionmentioning
confidence: 99%
“…The former 'Abbreviations: MGDG, DGDG, TGDG, and TTGDG, mono-, di-, tri-, and tetragalactosyldiacylglycerol, respectively; 1,2-DG, 1,2-diacylglycerol; UDGT, UDP-galactose: 1,2-diacylglycerol galactosyltransferase; GGGT, galactolipid:galactolipid galactosyltransferase; TG, triacylglycerol; FFA, free fatty acid; 16:3, hexadecatrienoic acid; 18:3, a-linolenic acid; 16:0, palmitic acid; 16:1, palmitoleic acid; 18:0, stearic acid; 18:1, oleic acid; 18:2, linoleic acid. reaction is catalyzed by UDGT (5,11,19) and the latter by GGGT (4,10,26). GGGT can also synthesize TGDG and TTGDG, normally absent in plant leaves in vivo (5, 26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation